Ethylene perception via ETR1 is required in Arabidopsis infection by Verticillium dahliae - Tjamos, Sotirios E.; Paplomatas, Epaminondas J.; Pantelides, Iakovos S. (My University, 2010)
Vascular wilts caused by Verticillium spp. are very difficult to control and, as a result, are the cause of severe yield losses in a wide range of economically important crops. The responses of Arabidopsis thaliana mutant plants impaired in known pathogen response pathways were used to explore the components in defence against Verticillium dahliae. Analysis of the mutant responses revealed enhanced resistance in etr1-1 [ethylene (ET) receptor mutant] plants, but not in salicylic acid-, jasmonic acid- or other ET-deficient mutants, indicating a crucial role of ETR1 in defence against this pathogen. Quantitative polymerase chain reaction analysis revealed that the decrease in symptom severity shown in etr1-1 plants was associated with significant reductions in the growth of the pathogen in the vascular tissues of the plants, suggesting that impaired perception of ET via ETR1 results in increased disease resistance. Furthermore, the activation and increased accumulation of the PR-1, PR-2, PR-5, GSTF12, GSTU16, CHI-1, CHI-2 and Myb75 genes, observed in etr1-1 plants after V. dahliae inoculation, indicate that the outcome of the induced defence response of etr1-1 plants seems to be dependent on a set of defence genes activated on pathogen attack
Keywords: Verticillium; Verticillium dahliae; Dahliae isolates